AUDIT COMMITTEE CHAIR CHARACTERISTICS, AND AUDITOR DISMISSAL IN A GOING CONCERN CONTEXT - Sawani, Assma M. (International Journal of Accounting & Finance Review, 2021)
This study examines the role audit committee chair expertise may play in fostering audit quality. The 2002 Sarbanes–Oxley Act (SOX) was enacted to strengthen corporate governance practices in the United States; a fundamental part of this act addressed the audit committee structure and composition. Existing literature suggests that audit committee expertise may improve audit quality. In this study I use a logistic model to compare audit committee chair expertise characteristics for first-time going concern opinion firms that dismissed and did not dismiss the auditor after receiving the going concern opinion for the years 2008-2016 with that of firms that received clean opinions and dismissed or did not dismiss the auditor. I find that audit committee chairs with financial expertise, audit expertise, governance expertise and industry expertise are negatively associated with auditor dismissal. This suggests that firms with these audit committee chair expertise profiles may facilitate better audit quality. Moreover, the chair’s audit expertise, industry expertise and financial expertise are differentially significant in the going concern context indicating that these expertise types may temper management’s inclination to dismiss auditors after undesirable opinions. JEL Classification Codes: M41, M42, M49.